Kompetensi Guru PAI dalam Perencanaan, Pelaksanaan dan Evaluasi Penilaian Secara Autentik (Studi di SMA Negeri 2 Binjai) - Sumarna, Abdi; Maharani, Anggi Ditami; Audia, Rindi Irma (Yayasan Rahmat Islamiyah, 2024)
In conducting the assessment in accordance with the 2013 curriculum, a teacher is required to apply an authentic assessment in accordance with the Standards of Assessment. Teachers are also required to have the ability to make conformity between assessment techniques and assessment instruments which are the requirements of instruments that have been set in Permendikbud No. 66 of 2013. However, in fact teachers are difficult to make assessment instruments tailored to the form of assessment. This study aims to understand more about the ability of PAI teachers in conducting learning evaluation through non-test assessment (authentic assessment). In this study, researchers used qualitative research with case study research. The data collection techniques through interviews and documentation. The result of this research shows that PAI teacher in SMAN 2 Binjai has understood in doing authentic assessment planning through learning implementation plan (RPP). As for carrying out authentic assessment actually PAI teacher in SMAN 2 Binjai has been able, just because of lack of self motivation.